Observation on the ultrastructure morphology of HeLa cells treated with ethanol: Statistical analysis. (1st November 2016) - Al-Bagdadi, Fakhri; Young, Matthew J.; Geaghan, James P.; Yao, Shaomian; Barona, Humberto M.; Martinez-Ceballos, Eduardo; Yoshimura, Masami
ABSTRACT: It is estimated that 5.9% of all human deaths are attributable to alcohol consumption and that the harmful use of ethanol ranks among the top five risk factors for causing disease, disability, and death worldwide. Ethanol is known to disrupt phospholipid packing and promote membrane hemifusion at lipid bilayers. With the exception of mitochondria involved in hormone synthesis, the sterol content of mitochondrial membranes is low. As membranes that are low in cholesterol have increased membrane fluidity and are the most easily disordered by ethanol, we hypothesize that mitochondria are sensitive targets for ethanol damage. HeLa cells were exposed to 50 mM ethanol and the direct effects of ethanol on cellular ultrastructure were examined utilizing transmission electron microscopy. Our ultramicroscopic analysis revealed that cells exposed to ethanol harbor fewer incidence of apoptotic morphology; however, significant alterations to mitochondria and to nuclei occurred. We observed statistical increases in the amount of irregular cells and cells with multiple nuclei, nuclei harboring indentations, and nuclei with multiple nucleolus-like bodies. Indeed, our analysis revealed that mitochondrial damage is the most extensive type of cellular damage. Rupturing of cristae was the most prominent damage followed by mitochondrial swelling. Ethanol exposure also resulted in increased amounts of mitochondrial rupturing, organelles with linked membranes, and mitochondria localizing to indentations of nuclear membranes. We theorize that these alterations could contribute to cellular defects in oxidative phosphorylation and, by extension, the inability to generate regular levels of cellular adenosine triphosphate.